Polyester vascular prostheses — antibacterial and athrombogenic biomaterials. Part I. Two-stage modification of vascular prostheses - Karaszewska, A.; Bucheńska, J. (Polimery, 2012)
A two-stage modification of polyester vascular prostheses, DALLONŽH, based on poly(ethylene terephthalate) (PET), has been carried out, resulting in medical implants possessing antibacterial and athrombogenic properties. In the first stage of the modification the prostheses were grafted with acrylic acid, then in the second stage they were padded with a biocide: amikacin (aminoglycoside) or amoxicillin (penicillin derivative). The chemical character of the addition of carboxyl groups and biocide to vascular prostheses was confirmed by FT-IR and 13C NMR spectroscopy (Figs. 1, 2). It was observed that the degree of prostheses padding with the biocide (ZAmok, ZAmik) increases with an increased grafting degree (X) of acrylic acid, thus it depends on the amount of carboxylic groups introduced into the polymer chain (Table 1). The rates of biocide release from the prostheses into water, saline (0.9 % solution of sodium chloride) or to a buffer (citrate-phosphate) were also examined (Fig. 5). It was found that the biocide is released to these solutions gradually and in low concentrations.